Presence of Rickettsia Species in a Marginalized Area of Yucatan, Mexico - Gaspar Peniche-Lara; Bertha Jimenez-Delgadillo; Claudia Munoz-Zanzi; María Cárdenas-Marrufo; Carlos Pérez-Osorio; Juan Arias-León (Journal of Tropical Medicine)
In the state of Yucatan, Mexico, rickettsiosis has become a common vector-borne disease in the general population. Ectoparasite species such as Rhipicephalus sanguineus and Amblyomma mixtum have been identified as Rickettsia vectors in Yucatan by studies focused on the wild animal population in rural areas. There have been studies that have tried to determine the presence of Rickettsia species in ectoparasites collected in Yucatan, but these studies did not include marginalized areas, where living in close contact with domestic and peridomestic animals that carry ectoparasites is a high-risk factor for acquiring rickettsial infection or many other vector-borne diseases. We evaluated the vector diversity and the presence of Rickettsia species presence in the ectoparasite population that parasitizes domestic animals in a marginalized rural town of Yucatan, Mexico; we also evaluated the seroprevalence of rickettsial antibodies in the human population of this town in order to determine the prevalence of rickettsial infection. A total of 437 ectoparasites were collected from the study area. The tick specimens collected belonged to the species Rhipicephalus sanguineus (n=380, 49 positive), Amblyomma mixtum (n=3, 0 positive), Ixodes affinis (n=4, 0 positive), Ctenocephalides felis (n=33, 0 positive), and Trichodectes canis (n=17, 0 positive). Conventional polymerase chain reaction and sequencing were used to identify the DNA of Rickettsia. Six out of 354 (1.8%) serum samples were positive for antibody to R. typhi. The combination of low antibody titers and the presence of Rickettsia species infecting ectoparasite species found in the study area requires eco-epidemiological studies and the identification of potentially protective practices or habits.